Colonic and type IV jejunal atresias with apple-peel bowel segment as the content of right inguinal hernia: A case report - Makhija, Deepa P; Kumar, Abhijit; Gupta, Rahul K; Sanghvi, Beejal V; Mudkhedkar, Kedar P; Shah, Rujuta S; Khobragade, Manish P; Parelkar, Sandesh V (Journal of Neonatal Surgery, 2021)
Background: Colonic atresia is an uncommon entity. It may be associated with multiple anomalies. Case Presentation: We present a case, which was initially suspected to be jejunal atresia, but was found to have colonic atresia as well intra-operatively. The associated jejunal atresia with apple-peel configuration was present as the content of inguinal hernia. Conclusion: This case report highlights the rarity of the condition and the postoperative issues in the management of such patients.